Implementation of Story-Telling at "Kumawus" to Postmodern People In Minahasa Culture - Douglas Sepang (Jurnal Economic Resource, 2026)
This study examines the implementation of storytelling as an evangelistic approach to postmodern Minahasa within the cultural context of kumawus, a traditional funeral-related ritual. The research addresses the challenge of cross-cultural evangelism in a postmodern society that tends to reject doctrinal teaching but is receptive to moral narratives and personal experiences. Using an anthropological and theological framework, this study explores how cultural understanding can bridge the gap between Biblical teachings and local traditions. The method employed is qualitative-descriptive, focusing on the integration of Biblical storytelling—particularly narratives such as the resurrection of Lazarus and Jesus Christ—into the kumawus setting. Findings suggest that storytelling aligns with postmodern preferences for experiential and reflective learning, allowing individuals to derive personal meaning without feeling coerced into religious commitment. This approach fosters openness to Biblical values while respecting cultural identity and communal practices. The study concludes that storytelling serves as an effective strategy for “sowing” spiritual understanding, while leaving the process of conversion to the work of the Holy Spirit. It is recommended that missionaries prioritize cultural sensitivity, relational engagement, and narrative-based communication in similar contexts.